Edukasi Urban Farming, Budidaya Sistem Hidroponik, dan Konsep 3R untuk Siswa-Siswa Sekolah Dasar - Lestari, Nunik; Nurdian; Rezky; Putri, Sesilia; Samsuar (Abdi Techno, 2024)
Urban farming activities are not only useful for providing local food crops, but also provide benefits in forming superior character for those involved. A number of studies state that urban farming activities carried out by students at school can increase students' creativity, environmental awareness, cooperation, responsibility and discipline. Urban farming with a hydroponic concept that utilizes waste will provide more meaningful learning for students, because it not only introduces students to agriculture, but also applies the 3R concept (reduce, reuse, recycle) which is useful for waste management. This community service program aims to provide knowledge and skills for students and teachers at SD Negeri 69 Barru so they can cultivate plants through a simple hydroponic system using plastic waste, as part of urban farming education and the 3R concept, as well as creating educational facilities for students. This community service activity is carried out in 4 stages, namely the coordination, planning, implementation and evaluation stages, with the implementation using lecture, discussion and direct practice techniques. The results of this community service activity have fulfilled the program objectives, where after the implementation of the activity it has an impact on increasing participants' knowledge and skills in hydroponic cultivation; helping schools provide learning facilities for urban farming, hydroponics and the 3R concept; creating 3R awareness in schools by utilizing plastic waste; as well as creating green open spaces for educational facilities for students.